The influence of flexible working arrangements and work-life balance on job satisfaction: A double-layered moderated mediation model - Indradewa, Rhian; Prasetio, Agustinus Ayung (Jurnal Ekonomi dan Bisnis, 2023)
This study aimed to test the impact of flexible work arrangements on work-life balance and job satisfaction with moderating variables of work stress, emotional exhaustion, and improvement of personal work life. The method of collecting data was carried out boldly in Jakarta. The respondents studied were employees & students who applied the principles of flexible work arrangements from March to May 2023. The research population involved 229 respondents who live in the Jakarta-Bogor-Depok-Tangerang-Bekasi area. The analytical method used is PLS-SEM (Partial Least Square-Structural Equation Modeling) through the SmartPLS 3.0 application. The research results show that flexible working arrangements positively influence job satisfaction and work-life balance. Work stress does not have a moderating effect in the impact of flexible working arrangements on work-life balance. Work-personal life enhancement affect work stress. Work-life balance has a positive effect on job satisfaction. Emotional exhaustion has a moderating effect in the impact of work life balance on job satisfaction. Work-personal life enhancement impacts emotional exhaustion. The managerial implications of this research for human resource management in implementing flexible time policies for organizations and their companies. The flexible working arrangement also can benefit the company by reducing the cost due to the fee for renting a workspace. This research can contribute to make an efficiency in corporations.